HIGH SPEAKING SCORE ACHIEVERS’ PERCEPTION ON THEIR SPEAKING SKILL DEVELOPMENT - Fahmi Zen; Ali Ashari; Imam Wahyudi Karimullah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: Speaking is the most frequently skill used that it gives higher prestige than any other skill. This research used explanatory mixed quantitative and qualitative method. The 22 subjects were final-year students in English Department at Universitas Islam Malang. The subjects were final-year students whose speaking score are high. Online questionnaire and online interview utilized as the methods of collecting data. The quantitative instruments used were yes or no questions. The quantitative data were automatically analyzed in the google form and the qualitative data were transcribed in detail then were concluded. The findings showed that the subjects were mostly perceived that their speaking mastery level is high. All of the subjects wanted to speak English fluent and well; more than a half of them were willing to be a speaker in the seminar or in other program. The opportunity and time for practicing in speaking and non-speaking classes were perceived appropriate. Materials and activities were given well and exiting while the facilities in the speaking classes were perceived less. Also, it is found that high achievers didn’t interact with classmates and lecturers always in English; however, they didn’t have matter barrier and climate in the context of psychology and classroom.Keywords: High Achievers, Perception, Speaking Skill, Development